Consumers' attention on identification, nutritional compounds, and safety in heavy metals of Canadian sea cucumber in Chinese food market. Issue 11 (13th September 2020) - Song, Zhuoyue; Li, Hailun; Wen, Jing; Zeng, Yeda; Ye, Xianying; Zhao, Weibo; Xu, Tingting; Xu, Nenggui; Zhang, Danyan
Abstract: Background: Based on the consumers' attention issues of sea cucumbers, we aimed to complete comprehensive information of commercial Canadian sea cucumbers (CCSC), which sprang up extensively in Chinese food market. Results: CCSC were identified as Cucumaria frondosa and characterized based on the characteristics, nutritional compositions, and heavy metals. The abdomen and five internal tendons of Cucumaria frondosa were special orange. The average of soaking degree and water content, which consumers paid great attention to, was 2.8 ± 0.3 and 0.46 ± 0.09%, respectively. Proteins (56.4 ± 9.1%) and polysaccharides (12.2 ± 14.7%) were the principal nutrient component. In addition, there was a variety of free amino acids, in which arginine (70.1 ± 50.0 mg/100 g), glutamate (42.6 ± 23.9 mg/100 g), and alanine (32.2 ± 21.0 mg/100 g) were the main components. Phosphorus (P, 0.26 ± 0.05%), magnesium (Mg, 0.19 ± 0.07%), and kalium (K, 0.17 ± 0.08%) were the major mineral elements. Amount of heavy metal was within the safety limitation (5.5 ± 1.4 mg/kg). Furthermore, the active ingredients were positively correlated with size. Conclusion: The overall findings enriched the information of Cucumaria frondosa for consumers and suggested that the quality of Cucumaria frondosa was varied following commercial classification and size. Abstract : This paper would enrich the information of Cucumaria frondosa for consumers and suggest that the quality of Cucumaria frondosa was varied following commercial classification and size.